Development and Application of Fluid-Solid Coupling Similar Materials in Discharge Test of Old Goaf Water. (14th July 2020) - Li, Zhenhua; Ma, Mingxiao; Bao, Yongsheng
Abstract : To study the evolution law of the discharge pathway for the old goaf water in the Datong mining area, a new fluid-solid coupling similar material was developed based on the fluid-solid coupling similarity theory. In the developed similar material, sand and barite powder were used as aggregate, polyurethane and white portland cement as binder, and water and silicone oil as regulator. The effects of different proportions on mechanical properties and water physical properties of materials were obtained through the experiments. The results show that the strength of the developed material is mainly controlled by cement and polyurethane, the hydrophilicity is affected by silicone oil, and the permeability coefficient is mainly affected by cement and polyurethane. For grouting agent, cement can realize the overall control function, and polyurethane can realize the local control in a certain range. As an ideal fluid-solid coupling similar simulation material, the developed material can simulate rock mass with different permeability and different strength. Besides, this material has been successfully applied to an experimental study on the mechanism of old goaf water discharge in an extra-thick coal seam in the Datong mining area, and the development and evolution characteristics of the old goaf water discharge pathway is obtained. This new kind of fluid-solid coupling similar material is developed based on the fluid-solid coupling similarity theory, which is suitable for revealing the evolution law of discharge pathway for the old golf water in the Datong mining area.